Effects of nitrogen on yield and chlorophyll of potato (Solanum tuberosum L.) cultivars - Güler, Semiha (Bangladesh Journal of Botany, 2010)
Effects of nitrogen on the leaf chlorophyll (chl), yield and yield attributing characters of potato as tuber number and mean tuber weight were studied. Correlation coefficients between the investigated characters were determined. Five nitrogen rates (0, 150, 200, 250 and 300 kg/ha) and four potato cultivars (Burren, Slaney, Anna and Emma) were used in the study. First, second, third class tuber yields and total tuber yield, tuber number per plant, and leaf chl were significantly influenced by both nitrogen rate and cultivar, whereas mean tuber weight was affected only by cultivar. Maximum total yield was obtained at 200 kg N/ha. There was significant linear relationship between leaf chl and N applied (R2=0.91). There were significant correlations between chl and yield and yield related characters. Total yield significantly correlated with leaf chl. Correlations between first class yield and total yield as well as total yield and tuber number per plant were highly significant. Key words: Potato; Solanum tuberosum L.; Leaf chlorophyll; Nitrogen; Yield DOI: 10.3329/bjb.v38i2.5141 Bangladesh J. Bot. 38(2): 163-169, 2009 (December)